Conference Record of the Twenty Fifth IEEE Photovoltaic Specialists Conference - 1996 1996
DOI: 10.1109/pvsc.1996.564252
|View full text |Cite
|
Sign up to set email alerts
|

Cu(In,Ga)Se/sub 2/ based submodule process robustness

Abstract: n 1 ' 1 8 -V , = 11.61 V I, = 68.29 mA J, = 1.690 mAcm2 Fill Factor = 66.26 % ---1 -111 -L -5% Efficiency = 13.0 % -46 I ) -Temperature = 25.0°C -+CO Area = 40.40 cmz Irradiance: 1OOO.O WmA2 ABSTRACT Submodule efforts have resulted in improved module design concepts as is demonstrated by: (1) a world record 13% conversion efficiency for a 40.4 cm2 laminated 20 segment submodule, and (2) the ability to produce submodules of high FF (170%) without other substantial losses relative to reference devices. The quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However, as can be seen below, this was not found to be significant for device performance. Previous investigations have placed specific interconnect resistances in the range of 0:320:8 O cm for standard contacts and 0:120:2 O cm for laserformed contacts [9].…”
Section: Contact Resistancesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as can be seen below, this was not found to be significant for device performance. Previous investigations have placed specific interconnect resistances in the range of 0:320:8 O cm for standard contacts and 0:120:2 O cm for laserformed contacts [9].…”
Section: Contact Resistancesmentioning
confidence: 99%
“…1a and b). Although the process is used where mechanical patterning is not an alternative, direct benefits have been reported such as reduced interconnect resistivity [9,10]. Other researchers have found that the resistivity of CIGS-based interconnects is higher than direct Mo-ZnO contacts [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation